2015
DOI: 10.1063/1.4936611
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-compact and wide-spectrum-range thermo-optic switch based on silicon coupled photonic crystal microcavities

Abstract: We design, fabricate and experimentally demonstrate a compact thermo-optic gate switch comprising a 3.78µm-long coupled L0-type photonic crystal microcavities on a silicon-on-insulator substrate. A nanohole is inserted in the center of each individual L0 photonic crystal microcavity. Coupling between identical microcavities gives rise to bonding and anti-bonding states of the coupled photonic molecules. The coupled photonic crystal microcavities are numerically simulated and experimentally verified with a 6nm-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 26 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…If a new cavity or a set of them is added to the structure, the optical response cannot only be enhanced but also new functionalities of the system can be obtained. Photon hopping, which consists in the energy transference between adjacent cavities, is one of the most relevant properties of PMs that find its application in coupled-resonator optical waveguides [10][11][12], optical switching [13,14] or quantum information processing [15,16], among others. Furthermore, it has been shown that this energy transfer can be tuned depending on the inter-cavities conformation and on the morphology of the cavities themselves [17,18], leading to enhanced bandwidths and boosted Q-factors [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…If a new cavity or a set of them is added to the structure, the optical response cannot only be enhanced but also new functionalities of the system can be obtained. Photon hopping, which consists in the energy transference between adjacent cavities, is one of the most relevant properties of PMs that find its application in coupled-resonator optical waveguides [10][11][12], optical switching [13,14] or quantum information processing [15,16], among others. Furthermore, it has been shown that this energy transfer can be tuned depending on the inter-cavities conformation and on the morphology of the cavities themselves [17,18], leading to enhanced bandwidths and boosted Q-factors [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A primary PhC directional coupler is formed by introducing two parallel linear defects into PhCs close to each other. Using the PhC coupler, devices like optical switches [16,17] , optical diodes [18] , and wavelength division multiplexer (WDM)/demultiplexers [19] can be built.…”
mentioning
confidence: 99%